2019
DOI: 10.1111/his.13972
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastomas presenting in adulthood: a study of 39 patients with emphasis on histological features and skeletal distribution

Abstract: Aims Chondroblastomas (CB) are rare bone tumours that typically arise in the epiphysis/apophysis of long bones in skeletally immature patients. We explore the clinicopathological features of CB presenting in adults. Methods and results CB in patients ≥20 years of age were retrieved from our institutional archives. Thirty‐nine CB were identified (29 male/10 female; aged 20–54 years). Twenty (51%) cases occurred in long tubular bones, 10 (26%) in small bones of the feet, five (13%) in flat bones and four (10%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…6 A recent study by John et al described the histologic features in a series of 39 patients. 7 Our findings demonstrated some overall similarities to the above studies (Table 4). In our case files, we found that a small subset of chondroblastoma (15%) occurred in skeletally mature individuals, the majority were younger than 40 years old, it was more common in men than women, and the tumors tended to involve the short bones of hands and feet more than the long tubular bones—common sites for the younger population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…6 A recent study by John et al described the histologic features in a series of 39 patients. 7 Our findings demonstrated some overall similarities to the above studies (Table 4). In our case files, we found that a small subset of chondroblastoma (15%) occurred in skeletally mature individuals, the majority were younger than 40 years old, it was more common in men than women, and the tumors tended to involve the short bones of hands and feet more than the long tubular bones—common sites for the younger population.…”
Section: Discussionsupporting
confidence: 88%
“…From an anatomic perspective, we found that chondroblastomas of adults have a predilection for involvement of other unusual sites such as: vertebra, rib, and scapula, findings which were previously reported in both adult and younger populations. 6 -11 Chondroblastomas presenting in adult patients had similar clinical manifestations and radiologic findings to those presenting in younger individuals. Of note, perilesional bone marrow edema was common in our study (80%), similar to prior reports.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Histologically, it's characterized by sheets of round to ovoid cells with well-defined cytoplasm borders and grooved nucleus, eosinophilic chondroid matrix, and osteoclast like giant cells [2]. Differential diagnosis includes primarily giant cell tumor of bone.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an open physis does not impede the tumor to involve the epiphyseal cartilage (12). On the other hand, CBL in adults more frequently involves the flat bones and short bones of the hands/feet with an aggressive behavior compared to children (13). As both the tumors are located in the epiphyseal region, absence of a chondroid matrix often causes confusion.…”
Section: Discussionmentioning
confidence: 99%